2000
DOI: 10.1001/archpsyc.57.10.968
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Treatment of Psychotic and Behavioral Symptoms in Patients With Alzheimer Disease in Nursing Care Facilities

Abstract: Low-dose olanzapine (5 and 10 mg/d) was significantly superior to placebo and well tolerated in treating agitation/aggression and psychosis in this population of patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
392
1
12

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 539 publications
(424 citation statements)
references
References 46 publications
19
392
1
12
Order By: Relevance
“…Virtually all studies to date have considered only presence or absence of psychosis. However, when we alternatively considered two more restrictive thresholds of clinically significant psychosis from the NPIFthat have been used as criteria for entry into clinical trials of antipsychotic drugs (Street et al, 2000;Deberdt et al, 2005) F we found essentially the same results. These analyses suggest that our findings did not depend heavily on the criterion employed to classify AD subjects as psychotic.…”
Section: Comparison To Other Apoe E4 Ad Psychosis Studiesmentioning
confidence: 59%
See 2 more Smart Citations
“…Virtually all studies to date have considered only presence or absence of psychosis. However, when we alternatively considered two more restrictive thresholds of clinically significant psychosis from the NPIFthat have been used as criteria for entry into clinical trials of antipsychotic drugs (Street et al, 2000;Deberdt et al, 2005) F we found essentially the same results. These analyses suggest that our findings did not depend heavily on the criterion employed to classify AD subjects as psychotic.…”
Section: Comparison To Other Apoe E4 Ad Psychosis Studiesmentioning
confidence: 59%
“…To ascertain whether our results were dependent on a particular definition of psychosis, we repeated the multiple logistic regression analysis using two progressively more restrictive criteria that have been utilized for entry into trials of antipsychotic drug for patients with dementia: (1) score X3 on either the Delusions or Hallucinations item of the NPI, corresponding with moderate severity or frequency (Street et al, 2000); (2) NPI-Psychosis X6 (Deberdt et al, 2005). We also examined the effect of four concomitant medication classes on psychotic symptoms by simultaneously adding them as independent variables to the primary logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of an IM formulation of olanzapine may offer safety advantages in the parenteral treatment of agitation. Oral administration of olanzapine has been shown previously to control psychotic symptoms and behavioral disturbances in elderly patients with Alzheimer's disease (Clark et al 2001;Street et al 2000), and this drug has been especially recommended for patients with dementia who exhibit "sundowning" behavior (Expert Consensus Guideline Series 1998). Intramuscular delivery of olanzapine provides a rapidly acting treatment for agitation in aggressive or hyperactive patients or those refusing oral medication, and may confer the advantages that have been reported for other parenteral formulations over their corresponding oral preparations, such as rapid onset (Dubin et al 1985;Schaffer et al 1982) and higher steady-state plasma concentrations (Kahn et al 1990;Simpson et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Lorazepam is commonly used for treatment of acute agitation, and the benzodiazepines are currently among the few agents available in a parenteral formulation for treatment of agitation. Use of orally administered atypical antipsychotics such as olanzapine and risperidone has met with some success in treating behavioral disturbances in patients with dementia (Clark et al 2001;De Deyn et al 1999;Katz et al 1999;Street et al 2000). A parenteral formulation of a second-generation antipsychotic might offer some advantage over their corresponding oral formulations due to faster onset of effect and utility where the patient cannot, or will not, accept oral treatment (Bianchetti et al 1980;Schaffer et al 1982).…”
mentioning
confidence: 99%